Poetic Symbols of Muhammad Safdar Mir - Sumaira Mukhtar (بازیافت)
Muhammad Safdar Mir was famous Urdu poet of the 20th centaury. This article seeks to bring into light the symbols of Muhamamd Safdar Mir's poem that he created in his poetry. The critic has tried to open hidden meaning of symbols discovered by the poet during creative act. This article deals with the styles and techniques he had employed in his symbolic poetry.